Bifunctional Zn(ii) complexes for recognition of non-canonical thymines in DNA bulges and G-quadruplexes. Issue 8 (18th December 2014) - Siters, Kevin E.; Sander, Stephanie A.; Devlin, Jason R.; Morrow, Janet R.
Abstract : The aromatic pendent groups of Zn(ii ) tetraazamacrocyclic complexes were varied to study their role in the recognition of non-canonical thymines in a DNA bulge and in the human telomeric G-quadruplex. Abstract : Six Zn(ii ) complexes of derivatives of 1, 4, 7, 10-tetraazacyclododecane (cyclen) were studied for binding to DNA sequences containing non-canonical thymines, including a hairpin with a single thymine bulge (T-bulge) and a G-quadruplex (H-telo) containing thymine loops. The cyclen-based macrocycles contained pendents with either two fused rings to give planar groups including quinolinone (QMC), coumarin (MCC) and quinoline (CQC) derivatives or a non-planar dansyl group (DSC). Macrocyclic complexes with three fused rings including an anthraquinone pendent (ATQ) were also studied. All Zn(ii ) complexes were stable in solution at micromolar concentrations and neutral pH with the Zn(L)(OH2 ) species prevailing for L = QMC and CQC at pH 7.5 and 100 mM NaCl. Immobilized T-bulge or H-telo G-quadruplex was used to study binding of the complexes by surface plasmon resonance (SPR) for several of the complexes. For the most part, data matched well with that obtained by isothermal calorimetry (ITC) and, for fluorescent complexes, by fluorescence titrations. Data showed that Zn(ii ) complexes containing planar aromatic pendents with two fused rings bound to T-bulge more tightly than complexes with non-planar pendents such as DSC. The H-telo DNA exhibited multiple binding sites for all complexes containing aromatic pendents. The complexes with two fused rings bound with low micromolar dissociation constants and two binding sites whereas a complex with three fused rings (ATQ) bound to three sites. This study shows that different pendent groups on Zn(ii ) cyclen complexes impart selectivity for recognition of non-canonical DNA structures.